FAKTOR MINIMUM KELOMPOK KECIL DAN KEPEMIMPINAN GEMBALA DENGAN PERTUMBUHAN JEMAAT DI GBI BANDENGAN JAKARTA - Ridwan Djaya; Rikardo P Sianipar (Sekolah Tinggi Teologi Bethel The Way Jakarta, 2022)
The purpose of this study was to find the corelation between the minimum factors according to Natural Church Development Small Groups and Pastoral leadership with congregational growth in GBI Bandengan. The method used in this research is quantitative using a survey with correlational techniques. Correlational research is a study that aims to examine the relationship and degree of relationship of two or more variabels. The sampling technique was carried out by probability (opportunity theory), which provides an equal opportunity for each population to be selected as a sample. The results of the study are as follows: (1) There is a relationship between Small Group NCD Minimum Factors and Congregation Growth in GBI Bandengan Jakarta, with a percentage of 39.7%. (2) There is a relationship between Pastoral Leadership and Congregation Growth at GBI Bandengan Jakarta, with a percentage of 43.3%. (3) There is a relationship between the Minimum Factor of small groups and Pastoral Leadership (X2) together with the growth of the congregation at GBI Bandengan Jakarta, the percentage is 56.4%. The conclusions in this study are that there is a positive relationship between the minimum factor of small groups and the growth of the congregation at GBI Bandengan; there is a positive relationship between pastoral leadership and church growth at GBI Bandengan; there is a positive relationship between the minimum factor of small groups and pastoral leadership with the growth of the congregation at GBI Bandengan.